Conglomerate Charge and Merchandise Swayed Inventory Model for Fragile Vendibles - Saarumathi R; Ritha W (The Scientific Temper, 2025)
Current business policy on marketing is very much challenging and competitive that every seller has to attract the customers by using various types of discount strategies. Apart from the common practice of trade and quantity discounts, the discount due to the pre-payment facility becomes a new trend in the market dynamics which is a motivation for every customer to buy goods. The inventory management considers customer’s demand as a key parameter which depends on certain factors like selling price, availability of the stock, time, quality of product, eco-friendliness of the product, impreciseness and so on. In the mathematical modelling for perishable goods the deterioration rate depends on certain factors like time, temperature, humidity, randomness etc. The optimal strategy of an inventory system for perishable goods with hybrid demand dependent on selling price and stock under the partial backlogging with a certain fixed ratio is fulfilled through Ranking Index method on Cloudy Normalised Triangular Fuzzy Number.